Lemon Aroma Therapy For Overcoming Nausea Vomiting At first Trimester Pregnancy Clinic Primary Afiyah In Pekanbaru: Lemon Aroma Therapy For Overcoming Nausea Vomiting At first Trimester Pregnancy Clinic Primary Afiyah In Pekanbaru - Risa Pitriani (Journal of Midwifery and Nursing, 2020)
One of the problems that occur in pregnancy is nausea, vomiting. Nausea, vomiting experienced by almost all pregnant women can arise at any time and not only in the morning. Usually occurs in first trimester pregnant women (0-12 weeks). Treatment efforts to overcome vomiting nausea are pharmacological and non pharmacological therapies. Pregnant women still use pharmacological therapy. One of the non-pharmacological is aroma therapy. A case study method in first trimester pregnant women complaining of nausea and vomiting, and to overcome the problem the writer tried to administer lemon aroma therapy. Taking the case was carried out by visiting the Primary Afiyah Clinic. blessed on Jl. Fajar IV No. 1 Labuh Baru, Payung Sekaki District, Pekanbaru City. Obstetrics Care for first trimester pregnant women with the aroma of lemon therapy to treat nausea and vomiting in the Pratama Afiyah Clinic is carried out using the SOAP documentation approach. The results of the first visit to mothers experience nausea and vomiting with a frequency of 6 times in 24 hour. After midwifery care for 4 visits to patients, the results obtained in the last study were the mother did not experience vomiting and the frequency of nausea 3 times in 24 hours and the result of nausea vomiting can be reduced. It is recommended that the Primary Afiyah Clinic not only provide pharmacologists but also provide non-pharmacologists to treat nausea and vomiting.